Increased IFN responses drive myeloid cell activation in people living with HIV-1 - Léo Plaçais; Candie Joly; Vanessa d’Urbano; Annamaria Paolini; Marie Bitu; Christelliah Mouanga; Katia Bourdic; Delphine Desjardins; Delphine Bredel; Katia Bourdic; Nathalie Chaput; Béatrice Jacquelin; et al. (Scientific Reports)
Abstract People living with HIV and who initiated antiretroviral therapy (PLH) at the chronic stage of the infection are generally exposed to persistent inflammation. We here assessed the impact of the interferon (IFN)/JAK-STAT pathway on myeloid cells from PLH and the potential of a JAK1/2 inhibitor, Baricitinib, to prevent IFN-driven myeloid cell activation. Peripheral blood mononuclear cells (PBMCs) from 16 chronically infected and virologically suppressed PLH were compared to 15 healthy uninfected individuals (UI) before and after exposure to type 1 IFN, type 2 IFN, and Baricitinib. First, we report an increased activation profile on monocytes and type 2 conventional dendritic cells (cDC2s) from PLH compared to UI, associated with a higher expression of PD-L1 and CD11b ex-vivo, and elevated transcription of pd-l1, cxcl-10 and ifnar1. Then, we unveil the role of type 1 and 2 IFN as inducers of PD-L1 expression at the transcriptional and protein level and highlight an increased response to IFN in PLH myeloid cells, associated with the delay before antiretroviral therapy initiation and the level of CD4 T cell depletion. Last, we describe the preventive effects of Baricitinib on IFN-driven PD-L1 expression. Our study shows that PLH harbor signs of myeloid cell activation, associated with increased type 1 and 2 IFN-signaling, which could be reversed by JAK1/2 inhibitors in vitro.